2017
DOI: 10.1590/0366-69132017633672131
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of soil-cement bricks with incorporation of used foundry sand

Abstract: In order to contribute to the sustainability of the foundry and construction industrial sectors, this work investigated the possibility of employing used foundry sand (UFS) in soil-cement bricks. Modular bricks were prepared with percentages of 10 wt% cement, 0-25 wt% commercial sand, 0-65 wt% used foundry sand, 25-65 wt% clay, and 15-30 wt% gravel dust. A content of 10 wt% Portland cement was adopted to ensure economic feasibility, and gravel was used to improve mechanical strength. The modular bricks were te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 9 publications
0
8
0
4
Order By: Relevance
“…Jordan et al ( 2019) studied soil-cement blocks with and without the addition of sugarcane bagasse and observed that the lack of pre-treatment of the waste interfered with the physical and mechanical results of the block due to the presence of impurities and granulometric variables, which contributed to a decrease in the quality of the mixtures. Leonel et al (2017), when evaluating a mixture composed of 10% cement, 0-25% commercial sand, 0-65% foundry sand, 25-65% clay, and 15-30% gravel powder, observed a reduction in water absorption with the addition of discarded foundry sand combined with crushed stone, although the mechanical strength remained stable.…”
Section: Industrial Solid Waste In Soil-cement Blocksmentioning
confidence: 99%
See 1 more Smart Citation
“…Jordan et al ( 2019) studied soil-cement blocks with and without the addition of sugarcane bagasse and observed that the lack of pre-treatment of the waste interfered with the physical and mechanical results of the block due to the presence of impurities and granulometric variables, which contributed to a decrease in the quality of the mixtures. Leonel et al (2017), when evaluating a mixture composed of 10% cement, 0-25% commercial sand, 0-65% foundry sand, 25-65% clay, and 15-30% gravel powder, observed a reduction in water absorption with the addition of discarded foundry sand combined with crushed stone, although the mechanical strength remained stable.…”
Section: Industrial Solid Waste In Soil-cement Blocksmentioning
confidence: 99%
“…However, as for solubilization, the soil-cement brick with added grits presented constituents that are solubilized in concentrations higher than those allowed by NBR 10005 (ABNT, 2004b) in relation to the water potability pattern, realizing that this would impede the molding of soil-cement bricks. Leonel et al (2017) evaluated the incorporation of foundry sand into soil-cement bricks and found leaching values that did not exceed the limit established by NBR 10004 (ABNT, 2004a); therefore, the materials could be classified as non-hazardous. However, a solubilization test indicated that the phenol did not incorporate wastes; therefore, it is not an adequate component for the brick molding process.…”
Section: Industrial Solid Waste In Soil-cement Blocksmentioning
confidence: 99%
“…En este aspecto, los ladrillos de suelo-cemento surgen como una alternativa a los de arcilla cocida, una vez que el suelo es considerado como un material sustentable en la construcción, debido a su abundancia y su uso desde hace miles de años (NAGARAJ et al, 2014;RAJESH;SRAVAN, 2016). Entre las principales ventajas de este tipo material se pueden mencionar: que no pasan por un proceso de cocción y/o quemado, por tanto se requiere menor energía en su producción y se minimiza el uso de recursos naturales, reduciendo la liberación de dióxido de carbono a la atmósfera en un 80% (OTI; KINUTHIA; BAI, 2009; OTI; KINUTHIA, 2012); poco consumo de energía durante la extracción de los materiales, ya que estos ladrillos pueden ser producidos en el lugar de la construcción, reduciendo adicionalmente los costos de transporte (BARBOSA et al, 2019); su uso facilita el pasaje de las instalaciones logrando una ejecución más rápida y posibilitando la no utilización de mortero, además que su acabado final es superior a los tradicionales, aunque se recomienda la impermeabilización y una cobertura de acabado (OTI; KINUTHIA, 2012), y el costo de los ladrillos de suelo-cemento es menor comparado a los de arcilla cocida (LEONEL et al, 2017).…”
Section: Introductionunclassified
“…Estabragh et al (2011) reported that soil-cement bricks could be used for slope and landfill protection and also as a pavement base in highways. Leonel et al (2017) observed that brick resistance was affected by the composition, particle size distribution, and activity of each component of the mixture.…”
Section: Introductionmentioning
confidence: 99%